Growth pattern of freshwater bivalve mollusk Lamellidens marginalis (Lamarck, 1819) from the northwest Bangladesh - Nahar, DA; Islam, MR; Islam, MS; Jasmine, S; Mondol, MMR (Journal of Bio-Science, 2019)
Growth, morphometry and length-weight relationships of the freshwater mussel Lamellidens marginalis (Lamarck, 1819) was studied during January 2014 and May 2015. Sampling was carried out monthly and a total of 560 specimens were collected from Rajshahi district, northwest of Bangladesh. The recorded length -breadth and length-width relationships were B = 0.179 + 0.475L and W = 0.196 + 0.3163L respectively. The length-total weight, length-wet tissue weight, length-dry tissue weight, length-shell weight, length-dry shell weight relationships were W = 0.1241L2.9066, W = 0.0524L2.7377, W =0.0116L2.7849, W = 0.0533L2.9178 and W = 0.0391L3.0386 respectively. Monthly b values of length-lengths and length-weights relationships indicated a negative allometric growth pattern except length-shell weights relationships which showed an isometric growth of the mussel. This study is the first report on growth pattern of Lamellidens marginalis from Bangladesh and the results would be useful for fishery managers to impose adequate regulations for a sustainable fishery management of this species in the freshwater ecosystem in Bangladesh. J. bio-sci. 27: 121-132, 2019